Authenticated Communication in Crises: Toward an Infrastructureless Trust Model for Challenged Networks - Pouyan Fotouhi Tehrani and Eric Osterweil and Jochen H. Schiller and Thomas Schmidt and Matthias Wählisch (Paris, France ; IEEE Press, 2019)
Natural as well as human-caused disasters and catastrophes easily lead to chaos. Effective crisis communication and informing the public about the current situation can reduce chaos and maintain social resiliency. Communication, however, relies on a working physical infrastructure, which usually is broken in the incident area. Whereas first response teams and authorities benefit from special communication equipment, civilians do not and experience longer periods of being disconnected from the outside world. Even if messages come through occasionally, the communication is too intermittent to allow for channel-based trust models. TLS, for example, requires access to trusted third parties to authenticate data. In this position paper, we argue that end-to-end communication conflicts with disaster scenarios. We propose an approach that leverages information-centric networking (ICN) to authenticate risk and crisis communication in loosely connected communication systems. Our proposal makes use of spatiotemporal decoupling of data from their producers based on ICN for optimal message propagation in fragmented networks, while introducing a trust bootstrapping phase to enable off-line authentication. The data-oriented security model of ICN is used to tailor a trust model specifically for scenarios during which access to trusted third parties or data owners is not given and messages are relayed through untrusted parties.